The Issue of the Law-Enforcer's Capturing Happiness in His Private Life - (:unkn) unknown (ELSEVIER SCIENCE BV, 2015)
A police job has a peculiarity. It is appealing to the policeman; but it may exert psychological hazards, especially detrimental to private life. Marriages may suffer, accordingly. Those professionals who are happy in their homes actually appear to be just an auspicious minority. (C) 2015 The Authors. Published by Elsevier Ltd.
Keywords: Police job; cop; private life; wedding; spouse